The PERBANDINGAN HASIL ANALISIS METODE ELEMEN HINGGA BERBASIS SOFTWARE DENGAN SIMPLE SUPPORTED CALCULATION PADA KAPAL 50 PAX CRANE BARGE - Meida Perwira Antartika; Budianto Budianto; Muhamad Ari; Ketut Suastika (Politeknik Negeri Batam, 2020)
Today the use of the Finite Element Method for the analysis of the strength of a structure is increasingly popular. The method of analysis is generally made easy by using software. In this study an advanced storage platform construction structure was analyzed on the 50 PAX Crane Barge vessel. The structure of this vessel uses BV grade A steel. Profile in this forward storage construction platform, the structure withstand loads is 6.4 tons (3.2 tons portside and 3.2 tons startboard). Load conditions are considered to be static, dynamic and impact conditions. The structure of the forward storage platform uses the 75x75x6 L angle bar profile as the main amplifier, each 1829 mm apart. This main amplifier is connected directly to the plate, and functions as the main buffer of the load to be given. The results of the analysis using software in the form of von Mises stress, normal stress, and principal stress. As a verification, manual calculation is done using the Simple Supported Calculation method. In this study comparing von Mises stress, normal stress, and principal stress results of the Finite Element Method with stress results of Simple Supported Calculation. Keyword : Finite Element Method, Barge, Simple Stress Calculation